2012
DOI: 10.1007/s00414-011-0661-7
|View full text |Cite
|
Sign up to set email alerts
|

The survival of metallic residues from gunshot wounds in cremated bone: a SEM–EDX study

Abstract: The research and analysis of gunshot residues has a relevant role in the examination of gunshot wounds. Nevertheless, very little literature exists concerning gunshot wounds on charred material. In this study, 16 adult bovine ribs (eight still with soft tissues and eight totally skeletonized) underwent a shooting test with two types of projectiles (9 mm full metal-jacketed bullet and 9 mm unjacketed bullet). Each rib then underwent a charring process in an electric oven, reaching the stage of complete calcinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Considering that micro-CT is an invasive, but nondestructive technique, and that the proposed method allows only a presumptive identification of A two-sided p < 0.05 was taken to indicate statistical significance ns not significant GSR, positive results could and should be confirmed by a Bgold standard^method, such as environmental scanning electron microscopy coupled with an X-ray fluorescence energy-dispersive spectrometry [30,31], inductively coupled plasma mass spectrometry [32], and/or neutron activation analysis [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that micro-CT is an invasive, but nondestructive technique, and that the proposed method allows only a presumptive identification of A two-sided p < 0.05 was taken to indicate statistical significance ns not significant GSR, positive results could and should be confirmed by a Bgold standard^method, such as environmental scanning electron microscopy coupled with an X-ray fluorescence energy-dispersive spectrometry [30,31], inductively coupled plasma mass spectrometry [32], and/or neutron activation analysis [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Th ese experiments have clarifi ed that the amount is strictly correlated to the shooting distance (2,12,13). Th ere are many histochemistry (12-15) studies and electron microscopy methods who are accurate and precise for estimating fi ring distance (16,17). However, most of these studies, if not all of them, are not applicable in every day forensic work, mostly due to their cost, as well as a necessity for sophisticated and expensive equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on GSR in decomposed remains have been conducted on soft tissue [17,18], as well as on skeletonized remains [4,10,11]. A study by La Goo et al [18], used microwave digestion prior to ICP-MS to detect GSR of Pb, Ba and Sb in pigs shot multiple times.…”
Section: Introductionmentioning
confidence: 98%
“…A c c e p t e d M a n u s c r i p t 3 Studies on GSR or bullet residue in skeletonized remains [4,10,11,19] have found evidence of GSR up to 90 years decomposition. Fischbeck et al [11] showed the presence of Pb in a finger bone of a murder victim by using PIXE analysis when soft tissue was absent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation